2022
DOI: 10.3390/cancers14215341
|View full text |Cite
|
Sign up to set email alerts
|

Medical Device Advances in the Treatment of Glioblastoma

Abstract: Despite decades of research and the growing emergence of new treatment modalities, Glioblastoma (GBM) frustratingly remains an incurable brain cancer with largely stagnant 5-year survival outcomes of around 5%. Historically, a significant challenge has been the effective delivery of anti-cancer treatment. This review aims to summarize key innovations in the field of medical devices, developed either to improve the delivery of existing treatments, for example that of chemo-radiotherapy, or provide novel treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 197 publications
0
3
0
Order By: Relevance
“…The BBB remains an impenetrable obstacle for many new promising antineoplastic agents and limits the effectiveness of plenty of drugs delivered through the systemic route. The main alternatives to systemic route delivery comprise delivering the drug directly to the brain tissue through surgical intervention by cerebrospinal fluid, convection-enhanced delivery, or implants containing therapeutics [51][52][53]. The other examined approach is focused on enhancing the bioavailability of therapeutics in the brain tissue by facilitating their way through the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB remains an impenetrable obstacle for many new promising antineoplastic agents and limits the effectiveness of plenty of drugs delivered through the systemic route. The main alternatives to systemic route delivery comprise delivering the drug directly to the brain tissue through surgical intervention by cerebrospinal fluid, convection-enhanced delivery, or implants containing therapeutics [51][52][53]. The other examined approach is focused on enhancing the bioavailability of therapeutics in the brain tissue by facilitating their way through the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no long-term adverse effects of AMF or MHT treatment have been reported, and much of the existing data suggest that MHT is an overall safe intervention [ 9 , 10 , 14 , 95 ]. Most AMF generators approved for use in MHT produce MFs with frequencies far below the dangerous radio frequency range [ 10 , 96 ] and orders of magnitude below the frequencies used in routine MRI [ 97 ].…”
Section: Mht Workflowmentioning
confidence: 99%
“…13,14 Hyperthermia using magnetic fluid containing Fe 3 O 4 nanoparticles under an alternating current magnetic field has already been approved in EU for treatment of glioblastoma since 2011. 15,16 It has been also reported that hyperthermia treatment with bone cement containing Fe 3 O 4 powder suppressed the progression of cancer in clinical trials. 17,18 Furthermore, it has been reported that thermal stimulation promotes bone formation by enhancing osteoblast proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 98%